POLITICAL PROCESS DRIVERS OF CORRUPTION IN EASTERN EUROPE - Ada-Iuliana POPESCU (CES Working Papers, 2016)
Corruption stands as one of the many obstacles to the political and economic security of the Eastern European region. Thus, despite the political and economic instability in the region, Eastern European countries, in and outside of the European Union need to fight corruption collectively and individually. The task is difficult, but hope is justified because the causes of corruption in this part of the region are similar and anti-corruption expertise is available. We believe that a deeper analysis of corruption’s drivers can produce a better articulated and more efficient anti-corruption strategy. This strategy will create an anti-corruption infrastructure that will strengthen the Eastern European Partnership. As a prelude to the deeper analysis that we believe must be a part of this strategy, this paper identifies the main drivers of corruption in the Eastern European Partnership countries and explains why addressing these drivers will strengthen the Eastern European Partnership.